Analysis of Compliance Factors of Pregnant Mothers to Health Protocol Covid 19 when Containing Antenatal Care: Analisis Faktor Kepatuhan Ibu Hamil terhadap Protokol Kesehatan Covid 19 saat Melakukan Kunjungan ANC - Yunia, Yusi Ratna; Dinengsih, Sri; Novelia, Shinta (Jurnal Kebidanan Midwiferia, 2022)
WHO recommends regular pregnancy checkups 8 meetings. However, with the current condition of the Covid-19 pandemic still not over, routine checks can be reduced in intensity to just 6 times. In several regions in Indonesia, such as in Yogyakarta, 6 pregnant women who tested positive for Covid 19 were found, in Surabaya there were 123 pregnant women who were positive for Covid-19, in Gresik there were 20 positive pregnant women for Covid-19 and in the Lampung region there were also three pregnant women who were positive Covid-19. With the increasing number of pregnant women who are positive for Covid 19, compliance with health protocols must be tightened in which pregnant women are people who are vulnerable to Covid 19 transmission. , and family support. The Objectives: know the analysis of the compliance factor of pregnant women with the Covid 19 health protocol during an ANC visit. Analytical research using cross-sectional method. The sample in this study amounted to 100 respondents. The sampling technique used total sampling. The research instrument was a questionnaire. Data were analyzed using univariate and bivariate with chi square statistical test. There was no significant relationship between age and education (p value> 0.05), while knowledge and family support showed a relationship with covid 19 health protocol compliance with p value <0.05. Compliance with the covid 19 health protocol in pregnant women is influenced by knowledge and family support. It is hoped that health workers should increase couns